Brew Beauty e-Commerce System - nur atiqah,; Mohd Zainuri Saringat, (Applied Information Technology And Computer Science, 2025)
The beauty and cosmetics industry in Malaysia, despite its substantial revenue growth, faces challenges such as manual inventory management, limited customer reach, and a lack of sales analysis tools. This paper proposes the development of an e-Commerce system for Brew Beauty, addressing these challenges. The system aims to streamline operations, enhance customer experience, and enable online sales. Key objectives include designing an object-oriented e-Commerce system, developing a web-based platform, and conducting thorough testing. The proposed system encompasses modules for registration, login, inventory management, advertisement, order processing, payment management, feedback collection, and sales reporting. The expected results include improved efficiency, increased sales, and enhanced data security. This project holds significance in modernizing business operations, promoting accessibility, and fostering growth in the beauty industry.